2018
DOI: 10.1007/s10067-018-4030-5
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphism of rs9277535 in HLA-DP associated with rheumatoid arthritis and anti-CCP production in a Chinese population

Abstract: HLA-II molecules are critical in triggering human immune response, especially in activating CD4+ T cells. HLA-DP, belonging to HLA-II molecules, draws increasing attention for its role in presentation of viral antigen and autoantigen to T cells. Researches reported single nucleotide polymorphism (SNP) of HLA-DP associated with HBV infection and autoimmune diseases such as SLE. However, little is known about the relationship between HLA-DP and rheumatoid arthritis (RA). Rs9277535 is located in 3' UTR region of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Meanwhile, the activation of self-reactive CD4+ T cells is necessary, although not sufficient, for inducing autoimmune diseases. HLA-II molecules, especially in activating CD4+ T cells, are critical in triggering human immune response (Huang et al, 2018). Therefore, the regulation of T cell subsets is crucial in maintaining immune balance.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the activation of self-reactive CD4+ T cells is necessary, although not sufficient, for inducing autoimmune diseases. HLA-II molecules, especially in activating CD4+ T cells, are critical in triggering human immune response (Huang et al, 2018). Therefore, the regulation of T cell subsets is crucial in maintaining immune balance.…”
Section: Introductionmentioning
confidence: 99%
“…Rheumatoid arthritis (RA) is a complex genetic disease associated with many major histocompatibility complex (MHC) genetic factors [ 14 ]. The MHC region is divided into Class I (HLA-A, HLA-B, and HLA-C), Class II (HLA-DRB1, HLA-DQB1, and HLA-DPB1), and Class III (C2 et al) groups [ 15 ]. The Class II HLA-DPB1 gene locus, which encodes proteins that bind to small antigen peptides and carry them into the cell surface for presentation to CD4+ T cells, has crucial effects on the immune system [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study of 254 Chinese RA patients and 391 control subjects demonstrated that the HLA-DPB1 rs9277535 locus is associated with an increased risk of RA and with elevated serum anti-CCP levels [ 15 ]. However, we found here that the HLA-DPB1 rs9277535 polymorphism was associated with decreased susceptibility to RA in Chinese individuals.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, Hsin-Chou et al found that variants within the rs1431403 region increased the occurrence of rheumatoid arthritis (RA) (Yang et al, 2012). Upregulation of HLA class II expression is an RA clinical detection index, and some studies have shown that the risk of RA is closely related to HLA genetic polymorphism (Guthrie, Gammill, Madeleine, Dugowson, & Nelson, 2011;Huang et al, 2018;Soumya et al, 2012). Based on these findings, it was inferred that rs1431403 polymorphism increased the incidence of anembryonic pregnancy by inducing abnormal expression of HLA class II molecules, such as HLA-DP.…”
Section: Discussionmentioning
confidence: 99%